Sensitive Immunochromatographic Assay Using Highly Luminescent Quantum Dot Nanobeads as Tracer for the Detection of Cyproheptadine Hydrochloride in Animal-Derived Food - Li, Pan; Yang, Cuifeng; Liu, Beibei; Wu, Qin; Wang, Yulong; Dong, Sa; Zhang, Hanxiaoya; Vasylieva, Natalia; Hammock, Bruce D.; Zhang, Cunzheng (Frontiers in Chemistry, 2020)
Cyproheptadine hydrochloride (CYP), used as human and veterinary drug, has been used illegally as feed additive for food-producing animals, which could remain in food and jeopardize human health. There is a need for on-site detection of CYP residue in animal-derived food. In this study, a hapten was designed, and a specific monoclonal antibody (mAb) was developed to detect CYP with an IC50 of 1.38 ng/mL and negligible cross-reactivity (CR) for other analogues. Forthermore, a high sensitive immunochromatographic assay (QBs-ICA) was developed using quantum dot nanobeads as reporters. The assay showed the linear detection range (IC20-IC80) of 0.03-0.52 ng/mL, the limit of detection (LOD) and visual detection limit (VDL) reached to 0.01 and 0.625 ng/mL, respectively. Spiked recovery study in pig urine and pork confirmed that the QBs-ICA was applicable for on-site testing. This assay showed better sensitivity and speedy than the reported instrumental analysis and immunoassays.